Pengaruh Komitmen Organisasi Pemerintah Desa, Sistem Pengendalian Internal, Dan Partisipasi Masyarakat Terhadap Akuntabilitas - Ni Gusti Ayu Ekayanti (UNHI Press, 2022)
Accountability is something that is very important to be discussed considering the impact is very large for the village community. Many factors can affect accountability. This paper is made to see what factors can cause a decrease or increase in accountability. Implementers of village financial management techniques (PTPKD) in West Denpasar Regency as a whole were used as the research population. Selected 64 people to be used as research samples with regression analysis techniques. From the research conducted, it is revealed that accountability will be greatly influenced by a commitment within the organization, control within the organization, and community participation in various activities in the village.